Bovine hypodermosis is highly prevalent in Kazakhstan: Results of a first serological study - Christian Bauer; Marat Kuibagarov; Lyudmila A. Lider; Dinara M. Seitkamzina; Zhanbolat A. Suranshiyev (Veterinary World, 2023)
Background and Aim: Recent information on the occurrence of bovine hypodermosis in Kazakhstan is limited to the results of a few clinical studies in the northern and eastern regions. A first serological study aimed to obtain more data on its geographical distribution and to estimate the prevalence in this country.